Peer Reactions, Peer Behavior, Student Attitudes, and Student Deviance: a Comparison of College Students in Japan and the USA - Kobayashi, Emiko (Asian journal of criminology, 2019)
This study presents evidence on the cross-cultural generalizability of differential association/social learning theory by testing whether the causal processes of learning attitudes toward deviance, posited by the theory, are equally applicable, and the causal links, specified by the theory, are equally strong in two diverse cultures—the USA and Japan. Drawing on the literature concerning cultural variability in individualism-collectivism, we predicted that the effects of peer reactions to deviance and peer deviance on a person’s attitudes toward deviance should be stronger in Japan than in the USA, and that the mediating effect of a person’s attitudes on the relationship of peer reactions and peer deviance to a person’s deviance should be weaker among Japanese than among Americans. Analyses of comparable survey data from college students in the USA (N = 625) and Japan (N = 591) provide generally supportive, but somewhat mixed, evidence regarding our predictions. In both countries, peer reactions to deviance predicted student attitudes toward deviance more strongly than did peer deviance. Peer deviance strongly predicted student deviance, while peer reactions to deviance predicted less strongly, and the effects were mediated by student attitudes in both countries. Contrary to the hypotheses, peer reactions and peer deviance did not predict student attitudes more strongly in Japan than in the USA. Also, peer deviance predicted student deviance more strongly in the USA than in Japan. In agreement with the expectations, the relation between student attitudes and student deviance was stronger in the USA than in Japan.